2010
DOI: 10.5539/ass.v6n4p93
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement in Children Academic Motivation

Abstract: This study examined parental involvement in their children academic motivation with the objectives; to investigate the morally and financially involvement of the parents in their children academic motivation in rural areas at primary level. It was concluded that most of the parents are not well aware of their role for their children education. In addition their attitude is of irresponsible type, they do not take interest in their children education even they do not help children in their homework or making arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 6 publications
1
12
0
3
Order By: Relevance
“…The second highest weighted mean has 2.58 which indicated that students are motivated to learn. This is in line with Ghazi's (2010) findings which revealed that students were motivated when their performance are appreciated and praised by their parents. The last one was 2.56 which indicated that students know their strength.…”
Section: Instrumentsupporting
confidence: 90%
See 2 more Smart Citations
“…The second highest weighted mean has 2.58 which indicated that students are motivated to learn. This is in line with Ghazi's (2010) findings which revealed that students were motivated when their performance are appreciated and praised by their parents. The last one was 2.56 which indicated that students know their strength.…”
Section: Instrumentsupporting
confidence: 90%
“…Learners get motivated when their parents who appreciate and proud on their achievements and performance (Ghazi, Ali, Shahzad, Khan, & Hukamdad, 2010). Motivation has a great impact on students' success (Ozen, 2017).…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…The best known theoretical constructs that have been applied to measure travel motivation are Maslow's hierarchy of needs, Alderfer's Existence, Relatedness and Growth (ERG) theory, Herzberg's motivator-hygiene theory (Ghazi, Ali, Shahzad, Khan, and Hukamdad 2010) as well as push-pull theory, Iso-Ahola's escape-seeking dichotomy (1982) and the travel career ladder (TCL) approach (Pearce 1988). All of these theories agree on one thing -psychological and/or biological needs predispose people to travel.…”
Section: Travel Motivationmentioning
confidence: 99%
“…This finding is in line with the research by (Prabawa et al, 2014), where socio-economic parents play a role in improving student learning achievement. Therefore parents must be able to fulfill their children's daily learning needs (such as textbooks, exercise books, pens, pencils, and bags) to encourage their academic achievements (Ghazi, Ali, Shahzad, & Hukamdad, 2014).…”
Section: Direct Effect Of Parental Socio-economic Conditions On Studementioning
confidence: 99%